Un curso de actualización y cambios conceptuales en profesores de física - Pacca, Jesuïna Lopes de Almeida; Pacca, A.; Villani, Alberto (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
The behaviour of secondary school Physics teachers atari updating course was analysed; the results led to an indication of a conceptual change in their practice. The object of analysis and discussion was the actual pedagogical planning by the teacher. The dynamics developed in the course favoured the reelaboration of the teacher’s conceptions, not only in relation to Physics contents but also in relation to the students’ learning process; a conceptual change in three sequent phases could be characterized.